Plurilingual literary writings as tools to develop students’ creativity - Kruszyńska, Klaudia A. (Neofilolog, 2024)
In an era marked by rapid change, educators face a persistent call to nurture creativity in students, prompting them to explore innovative solutions. This study investigates the role of students’ plurilingual resources in fostering creativity within a foreign language classroom at secondary school level. Students collaboratively produced literary writings (songs, poems, and short stories) in which they applied their plurilingual resources (all of languages they knew). This case study employs a bottom-up approach to analyse students’ texts to determine whether facilitating the use of their diverse linguistic resources, including the blending of codes and modes, acts as a catalyst for creativity. The research results indicate that the foreign language classroom can indeed serve as a platform for students to engage in various forms of language creativity. The findings also suggest that encouraging students to utilize their diverse linguistic resources enhances language creativity. Additionally, the analysis highlights that the collaborative nature of the task supports the notion that exploring multiple solutions, rather than adhering to a single correct answer, fosters creativity. Furthermore, evidence indicates that creating a safe environment for learners is crucial for encouraging playful and unconventional language use for creative purposes.